GAMBARAN KEBIJAKAN PEMERINTAH TENTANG PEMBATASAN JAM OPERASIONAL PADA PEDAGANG KAKI LIMA DI KECAMATAN MUARA UYA (p3m.stiatabalong.ac.id, 2022)
During the COVID-19 pandemic, the government imposed a policy of Enforcement of Community Activity Restrictions (PPKM) in the hope that this policy could reduce exposure and break the chain of the spread of COVID-19, in the Instruction of the Governor of South Kalimantan No. Several indicators that form the basis for this research are a. Health protocol, b. Operational hours limit, c. Sanctions, d. Impact. The purpose of this study was to determine the description and impact of the policy of limiting operating hours: 1) To find out the description of the Policy on Restricting Operational Hours in Lumbang village, Muara Uya sub-district; 2) Know what impacts are felt by small traders as a result of the policy; observation, interviews, and documentation are processes in data collection and secondary data obtained from previous research, and on the internet media, data analysis using the verbatim method of all observations and interviews when the research was conducted, the subjects of this study were street vendors totaling five people. The results of the author's research show that the description of the policy of limiting operating hours includes health protocols, hours restrictions, and sanctions. The impact of the Operational Hours Restriction Policy felt by street vendors is on the economy in the form of decreased turnover or income. Keywords: Covid-19, PPKM, Operational hours restrictions